1996
DOI: 10.1111/j.1365-2915.1996.tb00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative fecundity and associated factors for two sibling species of the Anopheles gambiaecomplex occurring sympatrically in The Gambia

Abstract: For two sibling species of mosquitoes belonging to the Anopheles gambiae complex of malaria vectors, the effects of body size (wing length) and bloodmeal size (haematin excretion) on fecundity of wild females were investigated in The Gambia, West Africa. Freshly blood-fed individuals from sympatric populations of An.arabiensis and An.gambiae sensu stricto were sampled by collection at 07.00-09.00 hours from within bednets during July/August 1993, at the beginning of the rainy season. The possible confounding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…An initial experiment confirmed previous reports [22,23] that oviposition likelihood depended on the size of females and this observation was consistently repeated in the two subsequent experiments that examined this relationship in more detail (Table 3, Figure 2). This first experiment also showed that increased competition actually reduced the likelihood of oviposition, despite the increased insemination probability expected (Table 3).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…An initial experiment confirmed previous reports [22,23] that oviposition likelihood depended on the size of females and this observation was consistently repeated in the two subsequent experiments that examined this relationship in more detail (Table 3, Figure 2). This first experiment also showed that increased competition actually reduced the likelihood of oviposition, despite the increased insemination probability expected (Table 3).…”
Section: Resultssupporting
confidence: 85%
“…freeborni [21], recent field studies of An.gambiae have shown that large males are no more likely to fall out of mating swarms in copula than are small males [24]. Here, however, we have shown that the size of female An.gambiae has major impact on not only their fecundity [22,23] but also their chance of being chosen as mates by the males who compete intensely for the privilege. Under these laboratory conditions, female size is the major factor influencing mate choice by males within and between strains as well as the size of subsequent egg batches.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The relationship between wing length and body mass is variable, and its exact nature can differ between mosquitoes of different species, strain and rearing background (Nasci, 1990;Siegel et al, 1992;Siegel et al, 1994). Despite this limitation, Anopheline mosquito wing length has consistently been shown to be a significant predictor of traits such as fecundity and survival (Ameneshewa and Service, 1996;Hogg et al, 1996;Kittayapong et al, 1992;Lehmann et al, 2006;Lyimo and Takken, 1993), and thus was selected as a useful approximator of mosquito fitness for our purposes.…”
Section: Field Collection and Dissectionsmentioning
confidence: 99%
“…The relationship between wing length and fecundity was also signiÞcant and positive, but with lower correlation coefÞcients and higher variance, indicating that other factors also affect fecundity. Several other studies have shown a positive relationship between wing length (or other measures of body size) and fecundity (Livdahl and Sugihara 1984;Packer and Corbet 1989;Briegel 1990a,b;Reeves 1990;Bradshaw and Holzapfel 1992;Clements 1992, Siegel et al 1992Renshaw et al 1994;Hogg et al 1996). Koenraadt (2008) found that the cephalothorax length is the most reliable pupal parameter to predict adult male body size in Ae.…”
Section: Figmentioning
confidence: 95%